2006
DOI: 10.4049/jimmunol.176.10.5707
|View full text |Cite
|
Sign up to set email alerts
|

TCR trans-Rearrangements: Biological Significance in Antigen Recognition vs the Role as Lymphoma Biomarker

Abstract: V(D)J rearrangements occur within loci of TCR and BCR genes, thus generating the diversity of the AgR repertoire. In addition, interlocus V(D)J rearrangements occur, giving rise to so-called “trans-rearrangements.” Such trans-rearrangements increase the diversity of the immune receptor repertoire and can be expressed as functional chimeric TCR proteins on the surface of T cells. Although chimeric receptors are not pathogenic per se, the frequency of AgR trans-rearrangements correlates with the level of genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…To address this question, we determined whether interchromosomal V(D)J rearrangements between the TCR␥ and TCR␤ loci, which are located on chromosomes 13 and 6, respectively, were present in RAG1-S723C mutant thymocytes using a nested PCR approach. 41 Interchromosomal trans-rearrangement is a predictor of global chromosomal translocations [41][42][43][44] and occurs at elevated frequencies in thymocytes that harbor mutations in genes that predispose to lymphoid neoplasia, including ATM, [44][45][46][47] DNA-PKcs, 41 and Nbs1. 43,44 We detected PCR products corresponding to trans-rearrangements between TCR␥V3S1 and TCR␤J2 in RAG1-S723C mutant thymocytes as well as ATM-null thymocytes ( Figure 5A).…”
Section: The Rag1-s723c Mutation Leads To Interlocus Trans-rearrangemmentioning
confidence: 99%
“…To address this question, we determined whether interchromosomal V(D)J rearrangements between the TCR␥ and TCR␤ loci, which are located on chromosomes 13 and 6, respectively, were present in RAG1-S723C mutant thymocytes using a nested PCR approach. 41 Interchromosomal trans-rearrangement is a predictor of global chromosomal translocations [41][42][43][44] and occurs at elevated frequencies in thymocytes that harbor mutations in genes that predispose to lymphoid neoplasia, including ATM, [44][45][46][47] DNA-PKcs, 41 and Nbs1. 43,44 We detected PCR products corresponding to trans-rearrangements between TCR␥V3S1 and TCR␤J2 in RAG1-S723C mutant thymocytes as well as ATM-null thymocytes ( Figure 5A).…”
Section: The Rag1-s723c Mutation Leads To Interlocus Trans-rearrangemmentioning
confidence: 99%
“…It has been suggested that the absolute number of "innocent" trans-rearrangements with both breakpoints in TCR gene loci correlates with the risk of lymphoma, regardless of whether that risk is based on an inherited predisposition or acquired exposure. An assay of trans-rearrangements may serve as a biomarker of lymphoma risk (Lipkowitz et al 1992;Lista et al 1997;Kirsch 1997;Lopes et al 2001;Allam and Kabelitz 2006). An increased number of innocent trans-rearrangements involving TRA/TRD in pigs may thus indicate a higher risk of T-cell lymphoma than in humans.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of chemotherapy was transient, and the study in paediatric patients showed that higher levels were exhibited only in patients homozygous for the wild type of CYP3A4 (Lopes et al 2004). The results suggest that the absolute number of TCR trans-rearrangements may serve as a biomarker of genomic instability, genotoxic exposure and lymphoma risk (Lista et al 1997;Kirsch 1997;Allam and Kabelitz 2006).…”
Section: Introductionmentioning
confidence: 88%
“…These erroneous rearrangements can result in the juxtaposition of oncogenes with TCR regulatory sequences, which are recurrent in several T cell malignancies [Boehm and Rabbitts, 1989;Korsmeyer, 1992;Marculescu et al, 2006]. It has been suggested that the absolute number of interlocus rearrangements correlates with the risk of lymphoma [Kirsch, 1997;Lista et al, 1997;Allam and Kabelitz, 2006]. A high number of trans -rearrangements in horses may thus indicate a higher risk of T cell lymphoma than in humans.…”
Section: Discussionmentioning
confidence: 99%